INFECTIONS CAUSED BY ACINETOBACTER BAUMANNII IN CANCER PATIENTS - N. V. Dmitrieva; M. V. Eidelshtein; V. V. Aginova; Z. V. Grigorievskaya; I. N. Petukhova; I. V. Tereshchenko; N. S. Bagirova; S. A. Dyakova; T. A. Kalinchuk; A. I. Dmitrieva; E. A. Shek; E. Yu. Skleenova (Сибирский онкологический журнал)
The purpose of the study was to evaluate the frequency of isolation of multi-resistant Acinetobacter baumannii in cancer patients and identify the mechanisms of resistance to carbapenems.Material and Methods. We analyzed 942 strains of A. baumannii isolated from clinical samples of cancer patients in the period 2014–16. The level of resistance to ampicillin-sulbactam, piperacillin-tazobactam, ceftazidime, cefepime, imipenem, meropenem, ciprofloxacin, amikacin, and to other antibiotics was determined. Carbapenem-resistant (Car-R) strains were examined for the presence of carbapenemases.Results. Between 2014 and 2016, the number of strains resistant to: ampicillin-sulbactam was 95.5–74.6 % (p≤0.0001), piperacillin – tazobactam 64.3–98.1 % (p<0.01), ceftazidime – 66.1–44.3 % (p≤0.0001), cefepime – 94.7–98.3 % (p≤0.01), ciprofloxacin – 95.8–91.8 % (p<0.05), amikacin – 77.7–91.0 % (p≤0.0001). An increase in the number of Car-R strains from 77.2 % in 2014 to 84.1 % in 2015 (p<0.05) and up to 90.0 % in 2016 (p<0.05) was observed. The resistance to imipenem was 100 %. The analysis of 6 strains in relation to acquired carbapenemases revealed the production of serine carbapenemases of the OXA-23 group in 100 % of cases.Conclusion. A. baumannii remains to be highly resistant to almost all classes of antibiotics, and the resistance to carbapenems is caused by the production of carbapenemases OXA-23.